Error propagation in the characterization of atheromatic plaque types based on imaging. Issue 3 (October 2015) - Athanasiou, Lambros S.; Rigas, George; Sakellarios, Antonis; Bourantas, Christos V.; Stefanou, Kostas; Fotiou, Evangelos; Exarchos, Themis P.; Siogkas, Panagiotis; Naka, Katerina K.; Parodi, Oberdan; Vozzi, Federico; Teng, Zhongzhao; et al.
Highlights A methodology for propagating imaging and segmentation errors is proposed. The error propagated to plaque characterization methods is estimated. The methodology is applied to IVUS, OCT and MRI imaging data. A more realistic validation is performed using the proposed methodology.